Traumatic posterior fossa extradural hematoma: case report and review of literature - Songara, Abhishek; Patil, Harshad Govardhan; Nayaran, Sharadendu (International Surgery Journal, 2016)
Traumatic posterior fossa extradural hematoma (PFEDH) is rare lesion constituting less than 10% all extradural hematomas. Reliance on clinical findings alone is not recommended as these are nonspecific; it is advisable to conduct a computerized tomography (CT scan) of brain. The recommended treatment for traumatic posterior fossa extra dural hematoma is surgical evacuation soon after diagnosis because the posterior fossa contains vital structures. There have been an increasing number of cases of traumatic posterior fossa extra dural hematoma treated conservatively with good results both in children and in adults. The decision between surgery and observation is still controversial. In this article we present our experience in treating patients with traumatic PFEDH and discuss risk factors and outcome.